Femtosecond diffraction studies of solid and liquid phase changes in shock-compressed bismuth. Issue 1 (December 2018) - Gorman, M.; Coleman, A.; Briggs, R.; McWilliams, R.; McGonegle, D.; Bolme, C.; Gleason, A.; Galtier, E.; Lee, H.; Granados, E.; Śliwa, M.; Sanloup, C.; et al.
Abstract Bismuth has long been a prototypical system for investigating phase transformations and melting at high pressure. Despite decades of experimental study, however, the lattice-level response of Bi to rapid (shock) compression and the relationship between structures occurring dynamically and those observed during slow (static) compression, are still not clearly understood. We have determined the structural response of shock-compressed Bi to 68 GPa using femtosecond X-ray diffraction, thereby revealing the phase transition sequence and equation-of-state in unprecedented detail for the first time. We show that shocked-Bi exhibits a marked departure from equilibrium behavior - the incommensurate Bi-III phase is not observed, but rather a new metastable phase, and the Bi-V phase is formed at significantly lower pressures compared to static compression studies. We also directly measure structural changes in a shocked liquid for the first time. These observations reveal new behaviour in the solid and liquid phases of a shocked material and give important insights into the validity of comparing static and dynamic datasets.